Pólipos endometriais e seu risco de malignização: aspectos epidemiológicos, clínicos e imunoistoquímicos - Dias, Daniel Spadoto [UNESP]; Dias, Flávia Neves Bueloni [UNESP]; Dias, Rogério [UNESP]; Nahás Neto, Jorge [UNESP]; Nahás, Eliana Aguiar Petri [UNESP] (My University, 2013)
Endometrial polyps are neoformations that result from focal hyperplasia of the endometrial basal layer associated with hormonal hyperstimulation. Their pathogenesis is still unclear, and there is no consensus on their natural history, actual relevance as pathologic entities, and relationship with endometrial neoplasia. Endometrial polyps are the most frequent indication of surgical hysteroscopy, but their optimal management remains controversial. Therefore, an overview of this condition may help choosing the most adequate treatment strategies.

Pólipos endometriais são neoformações resultantes de uma hiperplasia focal da camada basal do endométrio associada a um hiperestímulo hormonal. Sua etiologia ainda não está bem estabelecida, não havendo consenso sobre sua história natural, seu real significado como entidade patológica e sua relação com a neoplasia endometrial. Os pólipos endometriais são a principal indicação de histeroscopia cirúrgica, sem que haja, no entanto, um protocolo definido para seu melhor manejo. Uma visão abrangente sobre essa condição pode auxiliar na escolha da conduta mais adequada.
Endometrial polyps and the risk of malignancy: epidemiological, clinical and immunohistochemical aspects
Keywords: Endometrium/pathology; Hysteroscopy; Immunohistochemistry; Endometrial neoplasms; Polyps/epidemiology/surgery; Endométrio/patologia; Histeroscopia; Imunoistoquímica; Neoplasias do endométrio; Pólipos/epidemiologia/cirurgia